48.1k views
4 votes
What is the result of subtracting the second equation from the first?

-2x + y = 0
-7x + 3y = 2

User Derick F
by
6.4k points

2 Answers

1 vote

Answer:

5x - 2y = -2

Explanation:

-2x - (-7x) = -2x + 7x = 5x

y - 3y = -2y

0 - 2 = -2

User Andi Giga
by
6.0k points
5 votes

Answer:

5x -2y = -2

Explanation:

-2x + y = 0

-7x + 3y = 2

Subtract the second equation from the first

-2x + y = 0

-(-7x + 3y = 2)

--------------------------

Distribute the minus sign

-2x + y = 0

+7x - 3y = -2

--------------------------

5x -2y = -2

User Badal
by
6.1k points